Stretagi Pengembangan UMKM Huyula Berbasis Collaborative Governance Dalam Mewujudkan Ekonomi Berkelanjutan di Desa Lembah Hijau Di Kecamatan Bonepantai Kabupaten Bone Bolango - Sofyan Alhadar; Ria Anggita Zen M; Aling S. Pawawo; Abdul Rahmad Mohammad Yunus; Shikdar Mohammad Riazul (Solo International Collaboration and Publication of Social Sciences and Humanities, 2025)
Objective: This study aims to analyze the development strategy of Huyula Micro, Small, and Medium Enterprises (MSMEs) based on collaborative governance to achieve a sustainable economy in Lembah Hijau Village, Bone Bolango Regency. Theoretical framework: The study is grounded on three main concepts: business development strategy, collaborative governance, and sustainable economy. Business strategy emphasizes innovation, managerial capacity, and digitalization; collaborative governance highlights multi-stakeholder collaboration; while sustainable economy integrates economic, and social. Literature review: Previous studies reveal that MSMEs are vital contributors to Indonesia’s economy, accounting for more than 60% of GDP and absorbing 97% of the workforce. However, they face challenges such as limited resources, weak managerial capacity, inadequate institutional infrastructure, and poor digital adoption. Methods: This research applies a descriptive qualitative approach, conducted over six months (June–October 2025). Data were collected through observation, semi-structured interviews with seven purposively selected informants (village government, community leaders, four MSME actors, and youth representatives), and focus group discussions (FGD). Results: The findings indicate that Huyula MSMEs remain at the start-up stage, constrained by managerial, marketing, and innovation limitations. Collaborative governance proved crucial, involving the village government as facilitator, MSME actors as innovators, local leaders as social legitimators, youth as digital promoters, and the private sectors as financing and distribution partners. The collaborative model strengthens human resource capacity, builds collective institutions, and integrates digital technology to expand market access. Implications: The study implies that collaborative governance fosters inclusive and sustainable economic practices, aligning with Sustainable Development Goals (SDGs) 8 (Decent Work and Economic Growth) and 12 (Responsible Consumption and Production). Novelty: This research contributes by formulating an ideal model of MSME development based on collaborative governance at the village level, integrating managerial empowerment, institutional strengthening, and digitalization.